El grito lascasiano: el infierno de las Indias entre el apetito y la regeneración (Altre Modernità, 2013)
Bartolomé de Las Casas exposes the crimes and the violence of the Spanish conquest of America to the emperor and the Consejo de Indias, in his Brevísima relación de la destruicion de las Indias. Juxtaposing the unarmed American peoples with the wild violence of the invaders, Las Casas argues that the process of the conquest is an apocalyptic scourge which has struck the indigenous peoples and is a cruel denial of the providential mission of the universal Christian Empire.